Analisis Faktor-Faktor yang Memengaruhi Sikap Pengguna Twitter Tentang Pemberian Informasi Pribadi dengan Menggunakan Metode Structural Equation Modeling (SEM) - Mega Noviany; Ari Kusyanti; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Twitter is one of social media that is liked by many people in Indonesia because twitter can make it easier for the user to interact with other user through a computer or mobile. Currently many users who give too much information on social media because they do not care about the privacy and security on the social media used. In addition party from twitter stated the existence of data theft in the form of the personal information of millions of Twitter users in the whole world. User attitude when providing personal information on twitter certainly influenced by several factors. This research aims to determine the factors that can affect the attitude of Twitter users toward the gift of personal information. The sample used in this research as much as 241 Twitter users toward the gift of personal information with aged 16-25 years in Indonesia. Data analysis methods in this research using Structural Equation Modeling. The results of this research shows the factors that can affect the attitude of Twitter users toward the gift of personal information is trust in provider. The results of this research also shows the existence of the suitability of the models in analyzing this research because the value of the Goodness of Fit in accordance with the criteria.